Instructional coaching : a partnership approach to improving instruction - Knight, Jim (NSDC : Corwin Press, 2007)
Instructional coaching focuses on research-based strategies that can improve a teacher's practice the most. This book offers coaching skills essential to instructional coaches: listening, observing, modeling, and collaborating; plus guidance for leveraging instructional interventions for effective instructional practice. Includes stories and quotes from coaches, plus chapter organizers, resources for deeper learning, forms, worksheets, checklists, logs, reports, and more.